A new species of Aplectana (Nematoda: Cosmocercidae) parasite of Pleurodema nebulosum (Anura: Leptodactylidae) from the Monte desert, Argentina, with a key to Neotropical species of the genus Aplectana - Piñeiro Gomez, Mauricio D.; González, Cynthya E.; Sanabria, Eduardo A. (Zootaxa, 2017)
Here we describe a new cosmocercid nematode, Aplectana nebulosa sp. nov., from the small and large intestines of Pleurodema nebulosum (Anura: Leptodactylidae), from the Monte desert of San Juan, Argentina. The new species belongs to the Aplectana group that possesses a gubernaculum and unpaired adcloacal papilla anteriorly to cloaca. It resembles A. membranosa, A. paraelenae and A. travassosi by the presence of four adcloacal papillae, but differs from those species by the following characters: number and arrangement of precloacal papillae; number and arrangement of postcloacal papillae; shape and size of spicules and gubernaculum, and by the presence of lateral alae in caudal region of males. The description of the new species is based on light microscopy and scanning electron microscopy (SEM) and we also provide a key to Neotropical species of Aplectana.